2021
DOI: 10.3390/rs13183638
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mining-Induced Geo-Hazard Mapping Using Random Forest: A Case Study of Liaojiaping Orefield, Central China

Abstract: Mining-induced geo-hazard mapping (MGM) is a critical step for reducing and avoiding tremendous losses of human life, mine production, and property that are caused by ore mining. Due to the restriction of the survey techniques and data sources, high-resolution MGM remains a big challenge. To overcome this problem, in this research, such an MGM was conducted using detailed geological exploration and topographic survey data as well as Gaofen-1 satellite imagery as multi-source geoscience datasets and machine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The subjective empowerment method uses the Analytic Network Process (ANP), which is a further extension of the Analytic Hierarchy Process (AHP) [43]. The traditional hierarchical analysis method is widely used, but in the eco-geological environment system, the indicators are not completely independent of each other [44]. Therefore, compared with the hierarchical analysis method, the network analysis method more reasonably considers the interaction between factors or adjacent levels.…”
Section: Weights Calculated With Anp Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjective empowerment method uses the Analytic Network Process (ANP), which is a further extension of the Analytic Hierarchy Process (AHP) [43]. The traditional hierarchical analysis method is widely used, but in the eco-geological environment system, the indicators are not completely independent of each other [44]. Therefore, compared with the hierarchical analysis method, the network analysis method more reasonably considers the interaction between factors or adjacent levels.…”
Section: Weights Calculated With Anp Methodsmentioning
confidence: 99%
“…Geological hazards are representative factors that are directly related to the EEQ of a region [44]. Only geological hazards caused by mining were counted in this research, which included 37 landslides, 3 landslides, 4 debris flows, and 12 ground collapses.…”
Section: Geological Disaster Densitymentioning
confidence: 99%
“…And there are four deep crustal fault zones (e.g., > 400 km in length in the study area), 9 deep fault zones (e.g., 100-400 km) and 38 big fault belts (e.g., 10-100 km). The distribution and name (serial number) of major faults in the study area are shown in Figure 1 (Right):Deep Crustal Fault Zones include Yifeng-Jingdezhen(1), Pingxiang-Guangfeng( 5), Ganjiang( 6) and Baitu-Dexing (11); Deep Fault Zones comprehend Qibaoshan-Fuchun(2), Qingyun-Xiangtun(3), Shangrao-Xiaoshan(4), Suichuan-Linchuan(7), Dayu-Nancheng(8), Yingtan-Anyuan(9), Huichang-Yunxiao(10), Yongping-Xunwu (12), and Ezhou-Jiujiang(13).…”
Section: Study Areamentioning
confidence: 99%
“…The samples for constructing and testing classifier were obtained from Gaofen satellite images, Google Earth high resolution imagery (2013 and 2017), and a field survey (2021). Nine spectral indices, including soil-adjusted atmospherically-resistant vegetation index (SARVI) [69], normalized difference water index (NDWI) [70], normalized difference buildup soil index (NDBSI) [71], brightness-greenness-wetness from Tasseled Cap Transform (TCT) [72], and hue-saturation-value from HSV transformation [53] were used as classifier feature variables. Table 2 shows the parameters of the RF classifier and corresponding validation metrics for three investigation years (2013, 2017, and 2021).…”
Section: Land Use Change Analysismentioning
confidence: 99%
“…Remote sensing (RS) image classification is a common tool for land use survey, which has become more robust with the introduction of machine learning algorithms [41][42][43][44][45][46]. Supervised machine learning algorithms have obtained promising results in mineral prospectivity mapping [47][48][49][50], geo-hazard mapping and geo-risk assessment [51][52][53][54], biomass estimation [55][56][57][58], and dust source susceptibility mapping [59,60].…”
Section: Introductionmentioning
confidence: 99%